2008
DOI: 10.1111/j.1365-2621.2007.01708.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of pomegranate rind powder extract in cooked chicken patties

Abstract: The radical scavenging activity, reducing power and phenolic composition of pomegranate rind powder extract (RP) were determined and antioxidant properties of RP was evaluated in cooked chicken patties compared with vitamin C (VC) during refrigerated storage. Freshly minced chicken meat were assigned to one of the following six treatments: control (meat without any antioxidant); RP 5, RP 10, RP 15 and RP 20 (5, 10, 15 and 20 mg equivalent RP phenolics 100 g )1 meat, respectively) and VC 50 (50 mg VC 100 g )1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(87 citation statements)
references
References 28 publications
7
78
0
Order By: Relevance
“…However, at the present time, suspected that synthetic antioxidants such as butylated hydroxyanisole (BHA), butylated hydroxytoluene (BHT), tert-butylhydroquinone (TBHQ) and propyl gallate (PG) have toxic and carcinogenic effects (Wei-Min Zhang et al 2009). For this reason, much attention has been devoted to natural antioxidants for their capacity to protect organisms from damage induced by oxidative stress (Naveena et al 2008). To find new natural sources of antioxidants, our attention was focused on lichens.…”
Section: Introductionmentioning
confidence: 99%
“…However, at the present time, suspected that synthetic antioxidants such as butylated hydroxyanisole (BHA), butylated hydroxytoluene (BHT), tert-butylhydroquinone (TBHQ) and propyl gallate (PG) have toxic and carcinogenic effects (Wei-Min Zhang et al 2009). For this reason, much attention has been devoted to natural antioxidants for their capacity to protect organisms from damage induced by oxidative stress (Naveena et al 2008). To find new natural sources of antioxidants, our attention was focused on lichens.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic antioxidants such as BHT (butrylhydroxytoluene), TBHQ (tert-butylhydroquinone) is limited due to their potential carcinogenic effects . Thus, in the processing of chicken meat products, there is increasing need for a natural way to minimize oxidative rancidity and extend shelf-life (Naveena et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, this antioxidant mechanism have confirmed as that reported for the antioxidant activity of plants extracts depends on the concentration of phenolic compounds (Farag et al, 1989). Naveena et al (2008) found that antioxidant power of peel pomegranate had linearly correlation with increase the concentration of phenolics contained reach to the level of 400 mg g −1 . In general, phenolic are the major plant compounds with high level of antioxidant activity, this activity could be due to their ability to adsorb, neutralize and to quench free radicals to protect the plant tissues against oxidative damage (Oyedemi et al, 2010;Duh et al, 1999).…”
Section: Discussionmentioning
confidence: 54%